2013
DOI: 10.1002/2013gl057320
|View full text |Cite
|
Sign up to set email alerts
|

On the statistics of urban heat island intensity

Abstract: [1] We perform a systematic study of all cities in Europe to assess the Urban Heat Island (UHI) intensity by means of remotely sensed land surface temperature data. Defining cities as spatial clusters of urban land cover, we investigate the relationships of the UHI intensity, with the cluster size and the temperature of the surroundings. Our results show that in Europe, the UHI intensity in summer has a strong correlation with the cluster size, which can be well fitted by an empirical sigmoid model. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
155
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(182 citation statements)
references
References 28 publications
15
155
1
Order By: Relevance
“…The hysteresis behavior of urbanization-related warming has recently been observed by Zhou et al [2013] using satellite-sourced temperature data for clusters of cities in Europe and is reproduced here using air temperatures averaged over Europe.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The hysteresis behavior of urbanization-related warming has recently been observed by Zhou et al [2013] using satellite-sourced temperature data for clusters of cities in Europe and is reproduced here using air temperatures averaged over Europe.…”
Section: Discussionmentioning
confidence: 53%
“…Santamouris [2007] summarized the UHI research on European cities from the past 15 years using ground-based stations and found large regional differences in UHI amplitude. Using satellite data, Zhou et al [2013] compared temperature in clusters of cities in Europe with that of their surroundings and found that the radiant surface temperature difference is seasonally depended, with summer having the highest temperature difference in most parts of Europe, and temperature contrasts between cities and their surroundings are larger in spring than in autumn.…”
Section: Introductionmentioning
confidence: 99%
“…Imhoff et al [16] examined 38 cities in the continental United States and found the SUHI intensity to be highest at midday in the summer and lowest in the winter. Zhou et al [17] examined all cities across Europe and made the same conclusion regarding the seasonal variability of the SUHI intensity. Imhoff et al [16] further found that the SUHI varies across eco-climatic regions, with strong positive values for cities in forest biomes and negative values for desert cities.…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, cropland daytime/nighttime LST during the calculation of SUHII was defined as background daytime/nighttime LST. Dependence of daytime/nighttime SUHII on background daytime/nighttime LST was also implemented [43].…”
Section: Discussionmentioning
confidence: 99%
“…The canopy UHI relates to the thin layer of the atmosphere between ground level and roof top height, and is usually described by air temperature; the boundary layer UHI relates to a layer above the canopy layer, and is also usually measured by air temperature; SUHI differs from canopy UHI and usually is measured by land surface temperature (LST) from satellite or airborne sensors through upwelling thermal radiance [33]. With advantages in spatially explicit coverage and high resolution, LST-based SUHI has been increasingly used in recent studies at multiple scales ranged from cities [34][35][36][37][38][39], countries [28,40,41], continents [42][43][44], to the whole world [45,46]. To accurately quantify UHI effects, a definition of urban areas and its surrounding suburban/rural areas is the first step.…”
Section: Introductionmentioning
confidence: 99%